Opportunities and Challenges of Local History Research in North Maluku - Abbas, Irwan (JURNAL SOCIUS, 2023)
This study explains things related to the writing of Local History in North Maluku. This study aims to explain the opportunities and challenges of writing local history, several studies that have been carried out by researchers (senior historians) and young researchers (junior historians). This research is a qualitative research type of library research. The steps are as follows: (1). Topic selection; (2). Information exploration; (3). Determine the research focus; (4). Collection of data sources; (5). Preparation of data presentation; and (6). Preparation of reports. The conclusion is that the historiography of local history is a study that is always interesting to study and discuss. Local history has a very important meaning for communities living in certain geographic areas. Local history is rich in local wisdom values as part of local culture and the nation's cultural heritage. Local history is indeed not a written work as an exercise, therefore historians are required to work more seriously and be extra careful with the mastery of auxiliary sciences so as to give birth to a quality historiography.